Resistensi pemilih mahasiswa terhadap politik uang - Maya Mustika Kartika Sari; Mi’rojul Huda; Warsono Warsono (Integritas: Jurnal Antikorupsi, 2023)
The practice of money politics damages the essence of fairness in democracy. It can encourage abnormalities in democracy if its practice is seen as acceptable by young voters. The perceptions and reactions of young voters about money politics can influence the implementation of democracy and fair state politics. This study aimed to examine the practice of money politics among young student voters in Surabaya and their resistance to it. This study also attempted to respond to a gap in the literature regarding resistance to money politics among young voters. The research method consisted of two stages; first, exploring the responses of young voters about money politics through focus group discussions, and second, specifically using the phenomenological method with various empirical experiences and individual awareness regarding various actions and responses to the practice of money politics. This study found that young student voters carried out acts of resistance to money politics but not with real resistance. Instead, they showed silent resistance. The resistance was shown through taking the act of not voting in the election as a form of distrust toward the candidates, and other actions such as taking counter-adaptive actions by accepting the money given but not choosing candidates who carried out money politics. The rationality of novice voters in rejecting money politics was driven by good political values but their lack of ability to put up a fight encouraged silent resistance.